Control System for an Object with Interval-Given Parameters: Quality Analysis Based on Leading Coefficients of Characteristic Polynomials; International Review of Automatic Control (IREACO); Vol. 11, № 4 - Chursin Yu. A. Yuri Alexandrovich; Sonkin D. M. Dmitry Mikhailovich; Sukhodoev M. S. Mikhail Sergeevich; Нурмухаметов Р. А. Руслан Александрович; Pavlichev V. V. Vsevolod Viktorovich (2018, 2018)
Title screen